Linguistic-cognitive analysis of discourse from cognitive grammar - Loayza Maturrano, Edward Faustino (2021)
This article proposes through the theoretical position of a branch of cognitivism: cognitive grammar, the cognitive strategy that the human being executes when using the language. The objective of the study is to logically graph the cognitive processes in the function of thinking-meaning, of expressing oneself linguistically. The application of the cognitive strategy of the use of language is made effective in the linguistic pragmatics of the sociolect of the Sars CoV-2 pandemic. The research methodology is qualitative of the discourse analysis type. The results show the cognitive nature of linguistic innovations and show the executive process in the thinking-meaning of the statements. The main conclusion is that the linguistic-cognitive analysis of the proposed discourse graphs and shows the cognitive condition of the language. It is recommended to apply the analysis model in the interpretation of various speeches.